Advancing gender equality and social inclusion in sustainable water-energy-food-ecosystem management - Zaremba, Haley; Estrada Carmona, Natalia; Elias, Marlene (2023)
The water-energy-food-ecosystem (WEFE) nexus is a cross-sectoral concept offering a holistic perspective of the interconnections among agriculture, energy production, water resources, and ecosystem health. However, most emerging nexus approaches have been narrowly focused on resource efficiency and technocratic ‘fixes’ that don’t adequately consider the impacts of resource use and development on diverse groups of resource users and managers. Critically, WEFE approaches often fail to ask who nexus innovations are actually serving: who is making decisions, on whose behalf, who is doing the work, who is bearing the risks or costs, and who is reaping the benefits? CGIAR’s NEXUS Gains Initiative is working to change that. Researchers at the Alliance of Bioversity International and CIAT searched the most comprehensive nexus knowledge hub, and found that of the hub’s 2,112 resources, only three were tagged with the keyword “gender”. A search on Web of Science further underscored how little attention GESI topics receive in the nexus literature. Of the search’s 2,013 unique research articles containing the keywords “nexus” AND “water” AND “energy” AND “food OR agriculture”, only 1.2% mention “gender”, 0.55%, mention “environmental justice”, and a mere 0.1% mention “social inclusion” in the abstract, title or keywords. Most open access materials remained heavily focused on biophysical challenges and technological solutions without considering how risks, costs and benefits associated with these technologies could affect different social groups in the short and long term.